Laplace transformation method for calculating the kinetics of isomerization of cyclopropane. - Quý, Trần Vĩnh; Độ, Nguyễn Đình; Văn, Nguyễn (Vietnam Journal of Chemistry, 2012)
In conventional procedures for calculating the rate of unimolecular reactions according to the RRKM theory, the computation of number of molecular quantum vibrational states and density of states by direct counting on computer, being the most important stage, becomes very complicated and cumbersome even for high power computer. The "double-faced" approach (using simultaneously direct counting and Whitten-Rabinovitch analytical equation) is not consistent and, naturally, leads to some errors. In this paper, unlike in the approaches mentioned above, we made use of the Laplace transform steepest descent method for computing the density of states and the number of vibrational states at different energies, then compute the rate constant (kuni/k¥) at finite pressure by the aid of the conventional procedure of the RRKM theory. The obtained results prove to be reliable.